Micro Research: Finding sustainable local health solutions in East Africa through small local research studies - MacDonald, N.E.; Bortolussi, R.; Kabakyenga, J.; Pemba, S.; Estambale, B.; Kollmann, K.H.M.; Adome, R. Odoi; Appleton, M. (Journal of Epidemiology and Global Health, 2015)
Background: Sub-Saharan African countries have urged grassroots input to improve research capacity. In East Africa, Micro Research is fostering local ability to find sustainable solutions for community health problems. At 5 years, the following reports its progress. Methods: The Micro Research program had three integrated components: (1) 2-week training workshops; (2) small proposal development with international peer review followed by project funding, implementation, knowledge translation; (3) coaching from experienced researchers. Evaluation included standardized questions after completion of the workshops, 2013 online survey of recent workshop participants and discussions at two East Africa Micro Research Forums in 2013. Results: Between 2008 and 2013, 15 workshops were conducted at 5 East Africa sites with 391 participants. Of the 29 projects funded by Micro Research, 7 have been completed; of which 6 led to changes in local health policy/practice. Micro Research training stimulated 13 other funded research projects; of which 8 were external to Micro Research. Over 90% of participants rated the workshops as excellent with 20% spontaneously noting that Micro Research changed how they worked. The survey highlighted three local research needs: mentors, skills and funding – each addressed by Micro Research. On-line Micro Research and alumni networks, two knowledge translation partnerships and an East Africa Leaders Consortium arose from the Micro Research Forums. Conclusion: Micro Research helped build local capacity for community-directed interdisciplinary health research
Keywords: Micro Research; Research capacity; Developing countries; Community health; Maternal child health; Global health